Estimation of Bank Erosion Due to Reservoir Operation in Cascade (Case Study: Citarum Cascade Reservoir) - Legowo, Sri; Hadihardaja, Iwan K.; Azmeri, Azmeri (Journal of Engineering and Technological Sciences, 2009)
Sedimentation  is  such  a  crucial  issue  to  be  noted  once  the accumulated  sediment  begins  to  fill  the  reservoir  dead  storage,  this  will  then influence the long-term reservoir operation. The sediment accumulated requires a serious attention for it may influence the storage capacity and other reservoir management  of  activities.  The  continuous  inflow  of  sediment  to  the  reservoir will decrease the capacity of reservoir storage, the reservoir value in use, and the useful  age  of  reservoir.  Because  of  that,  the  rate  of  the  sediment  needs  to  be delayed as possible. In this research, the delay of the sediment rate is considered based on the rate of flow of landslide of the reservoir slope. The rate of flow of the sliding slope can be minimized by way of each reservoir autonomous efforts. This  effort  can  be  performed  through;  the  regulation  of  fluctuating  rate  of reservoir surface current that does not cause suddenly  drawdown  and upraising as well. The research model is compiled using the searching technique of Non Linear Programming (NLP). The  rate  of  bank  erosion  for  the  reservoir  variates  from  0.0009  to  0.0048 MCM/year, which is no sigrificant value to threaten the life time of reservoir.Mean  while  the   rate  of  watershed  sediment  has  a  significant  value,  i.e:  3,02  MCM/year  for  Saguling  that  causes  to  fullfill  the  storage  capacity  in  40  next years (from years 2008).